PROPHYLAXIS OF ACUTE RESPIRATORY TRACT INFECTIONS IN CHILDREN WITH RECURRENT BRONCHOPULMONARY DISORDERS - A. Yu. Simonova (Вопросы современной педиатрии)
One of the most urgent problems of Russian pediatrics — high prevalence of acute respiratory infections — is analyzed in this article. The author characterizes a special group of «frequently ill children». Patients of this group are the most prone to recurrent bronchopulmonary diseases, due to special features of their immunological statuses. The article also contains a short literature review on pidotimod trials, which have proved this drug to be effective and safe in acute and recurrent bronchopulmonary diseases as well as in bronchial asthma. In the patients who were administered pidotimod the frequency of relapses of acute respiratory tract infections decreased, the duration of the disease course shortened significantly, as well as these patients required antibacterial and antifebrile agents more rarely and did not have complications of allergic diseases. Children with recurrent bronchopulmonary diseases and bronchial asthma receiving pidotimod were shown to have lower rate of relapses and normalization of immunological characteristics. It is important to mention that pidotimod do not affect results of peak flowmetry and improve results of «Asthma Control Test». Pidotimod usage during vaccination guaranteed uneventful course of post-vaccination period and stimulation of immune response. Long-term study of clinical efficacy and safety of pidotimod allowed to recommend this drug as preventive and medicinal measure in pediatric practice.